Phase 2 study of neoadjuvant durvalumab plus docetaxel, oxaliplatin, and S-1 with surgery and adjuvant durvalumab plus S-1 for resectable locally advanced gastric cancer - Yoon-Koo Kang; Jong Seok Lee; Hyung-Don Kim; Min-Hee Ryu; Young Soo Park; Hyungwoo Cho (Journal for ImmunoTherapy of Cancer)
Background Based on the phase 3 PRODIGY study, neoadjuvant docetaxel, oxaliplatin, and S-1 (DOS) have emerged as a viable treatment option for Asian patients with resectable locally advanced gastric cancer (LAGC). This phase 2 study evaluated the efficacy and safety of combining neoadjuvant durvalumab with DOS, followed by surgery and adjuvant durvalumab plus S-1 chemotherapy, for resectable LAGC.Methods Patients with LAGC with cT2/3N+or cT4Nany tumors were enrolled in this study. Patients with proficient mismatch repair protein (pMMR) tumors received three cycles of neoadjuvant durvalumab plus DOS, administered every 3 weeks, followed by surgery and adjuvant S-1 plus durvalumab (main study arm). The primary endpoints were the rate of pathologic complete regression (pCR) and safety. An exploratory arm evaluated patients with deficient mismatch repair protein (dMMR) tumors, who received three cycles of neoadjuvant durvalumab and tremelimumab, followed by surgery and adjuvant durvalumab.Results In the main study arm, 50 pMMR patients were enrolled, and received at least one dose of neoadjuvant treatment. The median age was 63 years, with 72.0% being men. 18 and 32 patients presented with clinical stage II and III tumors, respectively. 49 (98.0%) underwent surgery, with 45 achieving R0 resection. A pCR rate of 30.0% was observed, meeting the prespecified primary efficacy endpoint. With a median follow-up of 21.8 months, the 3-year progression-free survival and overall survival rates were 69.9% and 88.1%, respectively. 10% of patients experienced predefined unacceptable severe toxicities, including febrile neutropenia (n=3) and persistent G4 neutropenia (n=2) lasting more than 7 days, thereby meeting the primary safety endpoint. Nine patients with dMMR tumors were enrolled in the exploratory arm. All nine underwent surgery, with a pCR rate of 22.2%.Conclusions This study met its primary efficacy and safety endpoints. The combination of neoadjuvant durvalumab plus DOS, followed by surgery and adjuvant durvalumab plus S-1 chemotherapy, warrants further investigation in a phase 3 trial for Asian patients with LAGC. Clinical trial information: 04221555.